The influence of Cultural Congress on the preferences of the permanent collection of the National Art Gallery of Malaysia/ Wenyan Geng, Wan Samiati Andriana Wan Mohamad Daud and Azian Tahir - Geng, Wenyan; Wan Mohamad Daud, Wan Samiati Andriana; Tahir, Azian (Idealogy Journal, 2023)
Since Malaysia's independence, the government convened the National Cultural Congress in 1971, which discussed building national identity in Malaysia through the culture of various races. The National Art Gallery, as an official institution with policy overtones, maintains a permanent collection of artworks for the nation, showcases the work of local and international artists, and encourages the development of art in the community. Therefore, this study uses a quantitative approach to secondary research, using the Cultural Congress as a dividing line, and to statistically classify works from each of the five years before and after by comparing changes in the nationality of the artists, the medium of the works, and the subject matter of the works to verify whether the emergence of the Cultural Congress had a significant impact on the National Art Gallery's collecting preferences. The results of this study show that the National Art Gallery's collection of works by national artists has also been on the rise since 1971, particularly in terms of the number of works by Malay artists and indigenous subjects. This research helps to examine the influence of the Cultural Congress from different perspectives and to understand the role of social factors on the views and approaches of artists. In addition, the collection of the art gallery will be collated and summarised to understand the preferences of the collection in each period and thus provide insight into the prevailing genres and approaches to art.